Second-generation HIV surveillance: better data for decision-making - Rehle Thomas; Lazzari Stefano; Dallabetta Gina; Asamoah-Odei Emil (The World Health Organization, 2004)
This paper seeks to outline the key elements of the expanded surveillance efforts recommended by the second-generation HIV surveillance approach. Second-generation systems focus on improving and expanding existing surveillance methods and combine them in ways that have the greatest explanatory power. The main elements of this approach include: considering biological surveillance - HIV, AIDS, sexually transmitted infections (STIs) - and behavioural surveillance as integral components, targeting surveillance efforts at segments of the population where most new infections are concentrated - which might differ depending on the stage and type of the epidemic - and providing the rationale for the optimal use of data generated for monitoring the HIV epidemic and evaluating national AIDS control programmes. The paper emphasizes improvements in existing surveillance methodologies and discusses in detail crucial issues such as the validity of HIV prevalence data measured in pregnant women and linking HIV surveillance and behavioural data collection. In addition, a strategic partnership between second-generation surveillance and AIDS programme evaluation is proposed that stresses the complementary roles of these data collection activities in determining the effectiveness of prevention and care programmes and explaining the epidemiological trend data collected by sentinel serosurveillance systems. In conclusion, second-generation HIV surveillance systems provide a comprehensive, cost-effective and appropriate response to the information needs of AIDS control programmes. The implementation of such systems, including a better use of the data generated by the system, will ensure that national programmes are in the best possible position to respond to the challenges of the epidemic.